GE_GERICHTE P/21173/2016 vom 11. November 2024 - GE Cour de justice (2024)
LÉSION CORPORELLE PAR NÉGLIGENCE;PRINCIPE DE L'ACCUSATION;MISE EN ACCUSATION;IN DUBIO PRO REO | CP.125.al1; CPP.329.al2; CPP.333.al1; CPP.350.al1